ANALISIS PEMIKIRAN PAULO FREIRE TENTANG PENDIDIKAN YANG MEMBEBASKAN - Mariani Mariani (ADIBA : JOURNAL OF EDUCATION, 2025)
This writing is motivated by the criticism that arises against the education model that is doctrinal, docmatic and does not provide space for students. The concept of education based on the liberation paradigm is theoretically based on Paulo Freire's epistemology of the oppressed society. In Paulo Freire's famous book Pedagogy of the oppressed describes the concept of education systematically and completely, then has led to liberating education, namely education as a process of humanisation, suing bank-style education, education facing the problem of an alternative education, dialogue as a method in liberation and education as a process of conscientisation.